1975
DOI: 10.1002/1097-0142(197507)36:1<225::aid-cncr2820360125>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the central nervous system in non-hodgkin's lymphoma

Abstract: Twenty-four patients with non-Hodgkin's lymphoma and CNS involvement are presented. There were 7 cases with diffuse histiocytic lymphoma (HL), 9 with diffuse poorly differentiated lymphocytic lymphoma (PDLL-D), of whom 6 patients were in leukemic conversion, 5 patients with nodular poorly differentiated lymphocytic lymphoma (PDLL-N), and 3 cases with undifferentiated lymphoma (UL). CNS complications were noted only in Stage IV lymphoma; the prognosis was generally poor. Histiocytic lymphoma was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…Central nervous system involvement (CNS) is not a rare complication during the clinical course of non-Hodgkin's lymphoma (NHL) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently improved therapies for NHL have resulted in longer survival periods, which may increase the likelihood of developing CNS involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system involvement (CNS) is not a rare complication during the clinical course of non-Hodgkin's lymphoma (NHL) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently improved therapies for NHL have resulted in longer survival periods, which may increase the likelihood of developing CNS involvement.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6) Although we did not examine the cerebrospinal fluid of our patient, the collections of necrotic and denatured tumor cell-like scars in the arachnoid, and the absence of tumor cells in the aneurysm wall suggest that these aneurysms developed via intrathecal dissemination.…”
Section: Discussionmentioning
confidence: 85%
“…7) The most common neuropathological findings in patients with metastasis are infiltration of the leptomeninges, nerve roots, perivascular space, or brain parenchyma, which can result in both focal and generalized symptoms. 6,10) We report an extremely rare case of ruptured aneurysms on the distal middle cerebral artery (MCA) that may be attributable to mucosa-associated lymphoid tissue (MALT) lymphoma. The patient was successfully treated with vasoconstructive surgery using a superficial temporal artery (STA) graft.…”
Section: Introductionmentioning
confidence: 99%
“…In 5 of our own cases, lymphomatous infiltration of the bone marrow was seen at presentation. Law et al (1975) have suggested that lymphoma with retroperitoneal involvement might have predilection for CNS relapse, as was the situation with Case 1. One of our patients (Case 5), had testicular swelling as an initial symptom and Wolley et al (1976) proposed that that type of clinical presentation might predispose to CNS disease later.…”
Section: Discussionmentioning
confidence: 95%